2009
DOI: 10.2174/138920109789542084
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophytum borivilianum: A White Gold for Biopharmaceuticals and Neutraceuticals

Abstract: Chlorophytum borivilianum Santapau & Fernandes (Liliaceae) also known as 'Safed Musli' is a traditional rare Indian medicinal herb which has many therapeutic applications in Ayurvedic, Unani, Homeopathic and Allopathic system of medicine. Its roots (tubers) are widely used for various therapeutic applications. It is used to cure physical illness and weakness, as an aphrodisiac agent and revitalizer, as general sex tonic, remedy for diabetes, arthritis and increasing body immunity, curative for natal and postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…There are reports on improved production of medicinally important stigmasterol and hacogenin through in vitro cultures of C. borivilianum (Bathoju and Giri, 2012a and b). The HPTLC (high performance thin layer chromatography) and HPLC (high performance liquid chromatography) analyses were performed by various researchers for qualitative analysis of saponins and to standardize the saponin and sapogenin of C. borivilianum (Govindarajan et al, 2005;Joshi et al, 2000;Sreevidya et al, 2006;Thakur et al, 2009a Till date only a few studies have been reported on systematic isolation of saponins.…”
Section: Saponins Of C Borivilianummentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports on improved production of medicinally important stigmasterol and hacogenin through in vitro cultures of C. borivilianum (Bathoju and Giri, 2012a and b). The HPTLC (high performance thin layer chromatography) and HPLC (high performance liquid chromatography) analyses were performed by various researchers for qualitative analysis of saponins and to standardize the saponin and sapogenin of C. borivilianum (Govindarajan et al, 2005;Joshi et al, 2000;Sreevidya et al, 2006;Thakur et al, 2009a Till date only a few studies have been reported on systematic isolation of saponins.…”
Section: Saponins Of C Borivilianummentioning
confidence: 99%
“…C. borivilianum is widely growing species and an integral part of Ayurvedic, Unani, Homeopathic and Allopathic systems of medicine, where root of the plant holds principal place. Traditionally, safed musli is considered as general health promotive tonic and has been used to treat various male sexual disorders (Thakur et al, 2009a). The knowledge on indigenous uses of C. borivilianum have been mostly passed through oral communication from generation to generation in local spoken languages and left undocumented by various communities.…”
Section: Introductionmentioning
confidence: 99%
“…2 It was first reported in India in 1954 and reached rare status in nature due to over exploitation. 3 C. arundinaceum Baker, C. laxum R.Br., C. tuberosum Baker, C. orchidastrum Hook.f., p.p. non Lindl.…”
Section: Introductionmentioning
confidence: 99%
“…It is a remedy for diabetes, for rheumatism and joint pains 6 . It is antimicrobial, anti-inflammatory and antitumor agent 7 . The roots of plants are currently sold in market at a price of Rs.…”
Section: Introductionmentioning
confidence: 99%